Landing Styles Influences Reactive Strength Index without Increasing Risk for Injury - Guy-Cherry, Dana; Alanazi, Ahmad; Miller, Lauren; Staloch, Darrin; Ortiz-Rodriguez, Alexis (Sports Medicine International Open, 2018)
The aim was to determine which three landing styles – stiff (ST), self-selected (SS), or soft (SF) – exhibit safer landing mechanics and greater jumping performance. Thirty participants (age: 26.5±5.1 years; height: 171.0±8.8 cm; weight: 69.7±10.1 kg) performed five trials of three randomized drop jump (40 cm) landing styles including SF (~60° knee flexion), ST (knees as straight as possible), and SS. Knee flexion and valgus angles and kinetics were measured. An electromyography system measured muscle activity of the gluteus maximus, quadriceps, hamstrings, tibialis anterior, and gastrocnemius. Reactive strength index (RSI) was used to measure jumping performance. ANOVAs were used to compare the three landings. All landings differed in knee flexion (p<0.001; effect size (η2): 0.9) but not valgus (p=.13; η2:.15). RSI (mm·ms-1) showed differences for all jumps (p<0.001; η2: 0.7) with SS (0.96) showing the highest value, then ST (0.93), and SF (0.64). Ground reaction forces were different between jumps (p<0.001; η2: 0.4) with SF (1.34/bodyweight (bw)) showing lower forces, then SS (1.50/bw), and ST (1.81/bw). No between-jump differences were observed for EMG (p>0.66; η2: 0.3). No landing demonstrated valgus landing mechanics. The SS landing exhibited the highest RSI. However, the 1.8/bw exhibited by the ST landing might contribute to overload of musculotendinous structures at the knee.
Keywords: landing; knee; valgus; jumping; drop jump